DAMPAK STRESS KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KARYAWAN PADA PT. SRIWIJAYA AIR DI MAKASSAR - Salma Abdullah; Ampauleng Ampauleng (P3M STIEM BONGAYA, 2018)
This study aimed to analyze the effects of job stress and work motivation on employee satisfaction on Air PT.Sriwijaya Makassar. This research data obtained from questionnaires, literature studies and interviews with relevant parties in accordance penelitian.Teknik destination using multiple regression analysis to test the hypothesis, the F test and t test. Total sample of 53 employees using simple random sampling method.The data analysis method is used in hypothesis testing Multiple Regression Analysis.The results showed that the stress of work and work motivation simultaneously influence and significant impact on job satisfaction of employees at Air PT.Sriwijaya Makassar. Partially, variable work motivation is the most influential variable on job satisfaction.